Pengaruh Komposisi Campuran Biomassa dan Limbah Padat Perkotaan terhadap Karakteristik Pembakaran - Roswati Nurhasanah; Prayudi; Valencia Safir Maharani (Virtual of Mechanical Engineering Article, 2026)
Incineration is a key waste treatment technology in the pursuit of sustainable solutions, and the use of biomass as an alternative fuel either alone or mixed offers a pathway to improve combustion efficiency. This study explores how woodchips and municipal solid waste (MSW) behave during combustion when used individually and in mixed-fuel configuration laboratory scale conditions. Fuel characteristics were determined through proximate and ultimate analyses following ASTM standards. Combustion performance was assessed using temperature profiles, burning rates, the amounts of char and ash produced. The results show combustion behavior among the tested fuels. Woodchips demonstrated the most stable combustion, with the highest heating value 4,134 kcal/ kg, the lowest ash content of 0.91%, and peak temperatures reaching 1,095 °C. In contrast, MSW burned less consistently, producing lower peak temperatures between 913 °C and 992 °C, higher char yields of up to 3%, and ash contents exceeding 13%. When woodchips were mixed with MSW, combustion performance improved noticeably. Among the tested mixtures, the 75:25 woodchips:MSW ratio provided the most balanced results, achieving a peak temperature of 1,069.2 °C, char yields of 1.7–1.8%, and ash content of ash yield below ~6.5%, while maintaining stable combustion conditions. Elemental analysis further indicated that woodchips contained very low sulfur 0.06% and also nitrogen 0.05%, suggesting lower potential for emission formation. Mixed woodchips:MSW at a 75:25 ratio substantially reduced sulfur and nitrogen contents compared to pure MSW. Overall, these findings indicate that a 75:25 woodchip:MSW mixture offers a practical balance between combustion stability, residue reduction, and emission formation potential for small scale waste to energy applications.